Perception of Students in Pre-practice from the Faculty of Education on the Role of School Librarians in the Teaching and Learning Process - Domínguez Flores, Noraida (2016)
This article discusses the need for educating future teachers on the role of the school library in the processes of teaching and learning. Specifically, the need for future teachers to learn how to collaborate with the (ACE) library (ACE) school in the teaching of information skills. Whereas this need, developed a collaborative project that was integrated into a course of pre-practice for the Faculty of education of the University of Puerto Rico, with the participation of students of the course competencies information and technology of the Graduate School of science and information technology from the same venue. The findings ofthis research showed that future teachers librarians (as) lack of knowledge around the competencies of information, as well as on the role of the (ACE) school in the processes of teaching and learning. At the end of the project showed a positive impact on the perception of future teachers to the school library and futurecollaborative relationships that can develop after starting his professional career.